Das Emanzipationsedikt von 1812 in Preußen Der lange Weg der Juden zu "Einländern" und "preußischen Staatsbürgern" - Diekmann, Irene A. (Europäisch-jüdische Studien - Beiträge, 2013)
Two-hundred years after the issuance of the "Edict concerning the civil rights of Jews in the Prussian state," the thirteen essays in this volume examine the Prussian emancipation model with the benefit of previously unresearched sources. Starting from the situation facing Prussian Jews at the time of King Friedrich II, the contributors explore the question of what new options the Edict opened up for the Jews and which constraints they continued to face as before.